Pengembangan E-Learning Berbasis Google Sites Pada Materi Sistem Ekskresi Untuk Kelas XI SMA: (Development of Google Sites-Based E-Learning on Excretory System Material for Class XI High School) - Rialdy, Alfajar; Hamidah , Afreni; Natalia , Desfaur (BIODIK, 2026)
This research aims to: develop Google Sites-based e-learning media on the material of the excretory system of grade XI high school that is valid and suitable for use in the learning process based on the results of expert validation, biology teacher assessment, and student responses through the ADDIE development model. E-learning products are developed based on the analysis of the needs of teachers and students, then validated by material experts and media experts, and tested on students. The results of the study show that the development process has succeeded in producing learning media that is suitable for use. The validation of material experts in the final stage obtained a percentage of 95% with the category "Very Feasible", while the validation of media experts reached 98% with the category "Very Feasible". Teachers' assessments of e-learning showed a percentage of 91.25% in the "Very Good" category. The response of the students was also very positive, with a feasibility score of 96.87% in the small group trial and 93.84% in the large group trial. Thus, Google Sites-based e-learning is declared feasible to be used as an alternative learning media for Excretion System material in grade XI of high school. abstrak. Penelitian ini bertujuan untuk: mengembangkan media e-learning berbasis Google Sites pada materi sistem ekskresi kelas XI SMA yang valid dan layak digunakan dalam proses pembelajaran berdasarkan hasil validasi ahli, penilaian guru biologi, dan respons peserta didik melalui model pengembangan ADDIE. Produk e-learning dikembangkan berdasarkan analisis kebutuhan guru dan peserta didik, kemudian divalidasi oleh ahli materi dan ahli media, serta diuji cobakan kepada peserta didik. Hasil penelitian menunjukkan bahwa proses pengembangan berhasil menghasilkan media pembelajaran yang layak digunakan. Validasi ahli materi pada tahap akhir memperoleh persentase 95% dengan kategori “Sangat Layak”, sedangkan validasi ahli media mencapai 98% dengan kategori “Sangat Layak”. Penilaian guru terhadap e-learning menunjukkan persentase 91,25% dalam kategori “Sangat Baik”. Respon peserta didik juga sangat positif, dengan nilai kelayakan 96,87% pada uji coba kelompok kecil dan 93,84% pada uji coba kelompok besar. Dengan demikian, e-learning berbasis Google Sites dinyatakan layak digunakan sebagai alternatif media pembelajaran pada materi Sistem Ekskresi di kelas XI SMA.